Efeito do treinamento muscular inspiratório na exposição ácida e na variabilidade da frequência cardíaca em indivíduos com esofagite de refluxo - Bezerra, Patrícia Carvalho (2015)
BACKGROUND: Gastroesophageal reflux disease (GERD) is caused by the presence of gastric contents in the esophagus lumen, its etiology and pathogenesis is multifactorial, but depend on the integrity of the antireflux barrier at the junction gastric esophagus, composed of the lower esophageal sphincter and crural diaphragm. Like all skeletal muscles, the diaphragm can improve performance in response to training. Changes in cardiovascular autonomic function frequently associated with alterations of motility and sensitivity of the digestive system. The heart rate variability has been used as a resource for the measurement of the activity of the autonomic nervous system. OBJECTIVE: To evaluate the effect of inspiratory muscle training in acid exposure and heart rate variability in patients with reflux esophagitis. METHODS: This is a study a randomized, experimental and interventionist in humans. Held at the University Hospital Walter Cantídio (HUWC) with holders of erosive esophagitis, which were randomly divided into two groups: the no-load training group (NLT) and group training load (LT). The volunteers did inspiratory muscle training (IMT) three times per week, for 8 weeks. We evaluated symptoms of reflux, MIP, acid exposure of the esophagus by pH monitoring and the components of heart rate variability (HRV) in the time domain (SDNN, rMSSD, pNN50) and in the frequency domain (VLF, LF, HF) by electrocardiogram . Data were statistically analyzed by SigmaPlot, version 11.0 and the program GraphPad PRISM ® 6.0 RESULTS: 32 volunteers; the NLT group of 15 volunteers, seven men (46.7%) and 8 women (53.3%) aged 22-57 years, mean of 40.46 ± 10.30 years; the LT group of 17 volunteers and 4 men (23.5%) and 13 women (76.5%) aged 25-57, average of 43.41 ± 9.59 years. In CBT decreased the frequency and intensity of heartburn (p = <0.001) reduction of regurgitation frequency (p = 0.005) increase in MIP (p = <0.001) decrease the number of progressing to reflux proximal channel (p = 0.011), but did not change the acid exposure of the distal esophagus; variability in heart rate, VLF component increased (p = 0.028) and HF component is inversely correlated with the number of reflux had progression to proximal channel (r = -0.484; p = 0.047). In TSC group showed decrease in the frequency of heartburn (p = 0.039) and reduced the number of lying reflux (p = 0.013). CONCLUSION: IMT, with pressure linear load decreased the frequency and intensity of symptoms of GERD, increased MIP, reduced the number of proximal reflux, which correlated with improved autonomic function.